How do Local Revenue, Revenue Sharing, General Allocation, and Special Allocation Funds impact Regional Spending in West Nusa Tenggara? - Lulu jumkhairatul; Hadi Mahmudi; Siti Sriningsih; Leonard K. Cheng; Alexander Kalb; Ermawati, Ermawati (Journal of Social and Humanities, 2023)
Regional own-source revenue serves as a vital funding source for local government operations. The more revenue a region generates locally, the greater its capacity to meet regional expenditure requirements. Regional revenue and expenditure are also funded through the regional budget, which includes profit-sharing funds, general allocation funds, and special allocation funds. This study aims to analyze the impact of Regional Own-Source Revenue, Production Sharing Fund, General Allocation, and Special Allocation Fund on Regional Expenditures in West Nusa Tenggara Province during the 2017-2021 period. The research is quantitative-descriptive in nature, utilizing secondary data from the West Nusa Tenggara Province Regional Financial and Asset Management Agency (BPKAD). Data collection is conducted through documentation, and data analysis employs panel data regression with the EViews 10 analysis tool. The findings indicate that local own-source income, general allocation funds, and special allocation funds positively and significantly influence regional expenditures in West Nusa Tenggara Province. However, profit-sharing funds have a negative and significant impact on regional expenditures. The determinant test (R2) reveals an R-Squared value of 0.9888, indicating that 98.88% of the variation in regional spending in West Nusa Tenggara Province can be explained by the independent variables, while the remaining 2.22% is influenced by external factors not included in this study's model.